Improved x-ray mass attenuation coefficient (opacity) measurements for Fe, Ni and Au. (11th June 2021) - Huang, H; Sequoia, K; Yamaguchi, M; Boehm, K J; Engelhorn, K; Walker, J; Elsner, F; Tomlin, J; Farrell, M; Fontes, C J; Colgan, J P
Abstract: We compiled five of the most common x-ray mass-attenuation coefficient (opacity) databases into a single program: NIST-XCOM (Hubbell), NIST-FFAST (Chantler), CXRO (Henke), SNL (Biggs) and LLNL (McMaster). For the first time the opacity values in these databases are compared for Z = 1–92 and a photon energy range from 1 to 30 keV. This effort revealed that the databases are consistent only to ∼10%, and sometimes far worse, even for common elements. To improve on this database, we constructed a tabletop instrument (known as 'Autoedge') capable of measuring the opacity of metal foils to ∼1%–2% accuracy for a photon energy range of 3–17 keV. We measured the opacity of Fe, Ni and Au using this new instrument resulting in approximately a 4–5× improvement in the accuracy to which the areal density of foils can be inferred from the data. We found significant disagreement in the shape of the opacity spectrum just above the K edge for Fe and Ni. Our new measurements disagree with previous tabulations by an amount in excess of 10% at 100 eV above the K -edge, with the discrepancy disappearing at about 1.5 keV above the edge. This shape above the edge agrees well with recent synchrotron data from the international initiative on x-ray fundamental parameters (IIFP) work group, but has been a challenge to model from a theoretical perspective. In contrast, there is no such disagreement above the Au L -edge. The newly measured opacity values were compiled into an improved opacity database and can be used to support ultra-high-accuracy high energy density (HED) target-certification and x-ray filter calibration activities when used in combination with Autoedge.